Clinical application and economics of five short-acting combined oral contraceptives over five years of obstetrics and gynecology practice in China based on real-world study - J. Jin; J. Tang (Clinical and Experimental Obstetrics & Gynecology)
Objective: We aimed to better understand the clinical application and economics of five commonly used combined oral short-acting contraceptives (COCs) by analyzing big data collected from an obstetrics and gynecology hospital in China. The COCs studied included desogestrel ethinyl estradiol tablets (DSE), which was administered at a dose of 20 or 30 μg ethinyl estradiol, ethinyl estradiol cyproterone tablets (ECP), drospirenone ethinyl estradiol tablets (DRE; 21 pills/box), and drospirenone ethinyl estradiol tablets (II; 28 pills/box). Methods: This retrospective study included patients who were prescribed COCs from 2014-2018 in our obstetrics and gynecology hospital, which is affiliated with Fudan University. We analyzed patient characteristics, clinical indications, drug costs, and types of drugs often prescribed with COCs to identify factors influencing medication choice and use. Results: Data from 127,183 patients using COCs was analyzed. The most commonly prescribed COCs was ECP, accounting for 64.16% of all COCs use, while DRE was the second most commonly prescribed (23.13%). Most patients were 21- to 30-year-old (56.82%). ECP, DSE (30 μg), and DRE were most commonly used in the treatment of menstrual disorders, while DRE (II) was more frequently used for contraception. The second most common indication for DSE (30 μg) use was endometriosis, while it was polycystic ovary syndrome (PCOS) for ECP and DRE. DSE (20 μg) was used by only two patients in our study. The per capita cost of either dose of DSE was low: 34.95 ± 5.34 RMB for the 30 µg dose and 62.56 ± 0.00 RMB for the 20 µg dose. ECP was the second most affordable at a cost of 82.81 ± 10.63 RMB, while DRE and DRE (II) were considerably more expensive at 186.88 ± 23.88 and 265.98 ± 22.12 RMB, respectively. The rank of the total cost of therapeutic drugs per capita was similar to that of COCs per capita. Either dose of DSE was cheapest, followed ECP. Again, DRE and DRE (II) were the most expensive. Metformin hydrochloride was the mostly commonly drug prescribed in conjunction with ECP; 39.89% of patients took both medications. Spironolactone tablets, other hormonal agents, and various Chinese patent medicines were also commonly prescribed with a COC. Conclusion: The main clinical indication for the prescription of COCs in our hospital has not been contraception, rather menstrual disorders and conditions characterized by excess androgen (e.g. PCOS). ECP entered the market the earliest in China, it is approved for the greatest number clinical indications, and it appears in the medical insurance catalogue of China. Thus, it is the most widely used COCs in China. In addition to contraception, it is also widely used to treat polycystic ovary syndrome and endometriosis. However, the 30 µg dose of DSE is the most affordable in regards to total list price, and it is used for menstrual disorders, endometriosis, and contraception.Key MessagesCOCs are widely used in obstetrics and gynecology hospitals. They are not only a reliable method of contraception, but in China they are even more widely used to treat or manage a variety of other conditions. A total of five COCs are commonly used; each has advantages and disadvantages in regards to cost, when they were introduced in China, their presence in the medical insurance catalog, and the conditions they are commonly used to treat. At present, there are few published studies focusing on the clinical applications and economics of COCs in actual practice. In this study, we used “big” clinical data to explore the indications for use and drug economy of these key COCs. We thereby aimed to understand the decision-making process that occurs between doctor and patient to provide a theoretical basis for optimal treatment and resource allocation, while reducing the economic burden.Based on this data, we determined that compared to the available alternatives, ECP is the most commonly prescribed form of COC, which is most familiar to frontline Gynecologists and Obstetricians while possessing the widest range of approved clinical indications. Although the 30µg dose of DSE is the most affordable, ECP runs a close second. Combined with its other attributes, it is not surprising ECP is widely prescribed.